Sport coaching as a 'profession': challenges and future directions - Duffy, P.; Hartley, H.; Bales, J.; Crespo, M.; Dick, F.; Vardhan, D.; Nordmann, L.; Curado, J. (International Journal of Coaching Science, 2011)
The strategy of the International Council for Coach Education (ICCE) has placed the development of sport coaching as a profession at the core of the mission of the organisation. The authors examine the basis for this aspiration against criteria associated with established professions, taking into account the unique features of sport coaching. It is concluded that, at a global level, sport coaching does not meet a number of the traditional hallmarks of a profession, primarily due to its current position on key descriptors such as purpose, knowledge base, organisation and ethics. In addition, the lack of fit of traditional 'right to practice' provisions within the established professions is identified as problematic. Sport coaching status categories include volunteer coach, professional coach, and the preparatory category of pre-coach. It is suggested that sport coaching should define its future identity as a blended professional area, operating within the wider field